Cooperative Learning Using Team Game Tournament Method To Improve Students Learning Participation and Comprehension - Fika Fitriasari (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
This study aims to know the best practice cooperative learning method, that suitable for economics and business mathematics course learning in Muhammadiyah Malang University. The specific goals of this study are: (1) Improving students of class 1-D in Management Department of Muhammadiyah Malang University's learning participation in sequence and series subject matter using cooperative learning with Teams Games Tournament (TGT) method in the odd semester of 2017/2018, and also (2) Improving Improving students of class D in Management Department of Muhammadiyah Malang University's comprehension about sequence and series subject matter using cooperative learning with Teams Games Tournament (TGT) method in the odd semester of 2017/2018. The results of this study show that learning activities using Teams Games Tournament (TGT) method has been proven can improve student's learning participation and comprehension in sequence and series subject matter of economics and business mathematics course.